Deer herbivory reduces web-building spider abundance by simplifying forest vegetation structure - Roberson, Elizabeth J; Chips, Michael J; Carson, Walter P; Rooney, Thomas P (PeerJ Preprints, 2016)
Indirect effects are a common feature of ecological systems, arising when one species affects interactions among two or more other species. We examined how browsing by white-tailed deer (Odocoileus virginianus) affected the abundance and composition of a web-building spider guild through their effects on the structure of the ground and shrub layers of northern hardwood forests. We examined paired plots consisting of deer-free and control plots in Pennsylvania and Wisconsin. We recorded the abundance of seven types of webs, each corresponding to a family of web-building spiders. We quantified vegetation structure and habitat suitability for the spiders by computing a web scaffold availability index (WSAI) at 0.5 m and 1.0 m above the ground. At Wisconsin sites, we recorded prey availability. Spider webs were twice as abundant in deer-free plots compared to control plots, while WSAI was 7-12 times greater in deer-free plots. Prey availability was also higher in deer-free plots. With the exception of funnel web-builders, all spider web types were significantly more abundant in deer-free plots. Both deer exclusion and the geographic region of plots were significant predictors of spider community structure. In closed canopy forests with high browsing pressure, the low density of tree saplings and shrubs provides few locations for web-building spiders to anchor webs. Recruitment of these spiders may become coupled with forest disturbance events that increase tree and shrub recruitment. By modifying habitat structure, deer indirectly modify arthropod food web interactions. As deer populations have increased in eastern North America over the past several decades, the effects of deer on web-building spiders may be widespread throughout the region.
Keywords: white-tailed deer; exclosure; disturbance; trophic ricochet; non-metric multidimensional scaling; effect size; indirect effects; northern hardwoods; forest ecology